Formulasi Lip Balm Minyak Almond dan Ekstrak Biji Kesumba Keling (Bixa orellana L.) Sebagai Pewarna Alami: Lip Balm Formulation of Almond Oil and Kesumba Keling (Bixa orellana L.) Seed Extract as Natural Colorants - Hafifah Sarwanda; Nurul Fitriani; Niken Indriyanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
lip balm is a preparation used on the lips as a moisturizer and lip protector. there have been many innovations lip balm with moisturizers and dyes natural ingredients. In general, the lip balms on the market use chemicals that can cause irritation. Therefore, almond oil is used which is a natural oil as an emollient and the kesumba keling Plant is a natural dye derived from the extraction of the kesumba keling seeds. The method used was experimental research, namely the formulation of lip balm with various concentrations of almond oil. 5%, 10%, 15%, and 20% and stability testing of preparations covering organoleptic, homogeneity, pH, dispersibility, which was carried out for 28 days, in addition to that, the melting point test was carried out. The results obtained in the organoleptic test were reddish orange in color, a distinctive odor of lip balm, with a semi-solid consistency. Result of Homogeneity test is the absence of coarse grains (homogeneous). The result of pH test is pH of the lip balm preparation stable at pH 5. The result of spreadability test is a diameter range of 2.5 - 4 cm. And the result of melting point test is a range of 54 - 580C. Based on the evaluation results, the lip balm has better physical quality and is stable in the 20% almond oil lip balm formulation.